2003
DOI: 10.1103/physrevlett.90.100402
|View full text |Cite
|
Sign up to set email alerts
|

Local Information as a Resource in Distributed Quantum Systems

Abstract: A new paradigm for distributed quantum systems where information is a valuable resource is developed. After finding a unique measure for information, we construct a scheme for it's manipulation in analogy with entanglement theory. In this scheme instead of maximally entangled states, two parties distill local states. We show that, surprisingly, the main tools of entanglement theory are general enough to work in this opposite scheme. Up to plausible assumptions, we show that the amount of information that must … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
324
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 252 publications
(337 citation statements)
references
References 21 publications
10
324
1
2
Order By: Relevance
“…The most sophisticated case is the two-way communication scenario C =↔ (sometimes called ping-pong protocol) [25].…”
Section: A Protocolsmentioning
confidence: 99%
“…The most sophisticated case is the two-way communication scenario C =↔ (sometimes called ping-pong protocol) [25].…”
Section: A Protocolsmentioning
confidence: 99%
“…Or, equivalently, How large is quantum deficit for a given state? For pure state the answer is known [2]: the amount of information that cannot be localized is precisely entanglement of formation of the state [6], given by entropy of subsystem. However, for mixed states even separable states can have nonzero deficit.…”
Section: Introductionmentioning
confidence: 99%
“…In recent development [1,2] an idea of localizing information (or concentrating) in paradigm of distant laboratories was devised. It originated from the concept of drawing thermodynamical work form heat bath and a source of negentropy (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We also derive the best transformation efficiencies. [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22] which operate either in a deterministic or probabilistic way. Corresponding to the quantum no-cloning theorem, Pati and Braunstein [23] demonstrated that the linearity of quantum mechanics also forbids one to delete one unknown state ideally against a copy [23], which is called the quantum no-deleting principle.…”
Section: Introductionmentioning
confidence: 99%